Experiences of Management Activities in University Teaching - Carolina da Costa Santos; Fátima Pereira; Amélia Lopes (Universidade Federal do Rio Grande do Sul, 2018)
Bearing in mind the context of transformations in, and of the, Higher Education and the intensification of professors' work, this paper debates academic management in the daily routines of university professors in regard to teaching, research and extension. The discussion focuses on the experiences of 23 university professors, from Brazil and Portugal, collected through biographic interviews. Amongst the positive features of management are the possibilities to democratically participate in the university's decision making and of a clear view on the functioning and structuring of higher education. The convergence between management with bureaucratic and administrative activities is seen as a negative feature, leading to a depreciation and discredit of management.